Phase 2 trial of bortezomib in combination with rituximab plus hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone alternating with bortezomib, rituximab, methotrexate, and cytarabine for untreated mantle cell lymphoma. Issue 12 (3rd May 2018) - Romaguera, Jorge E.; Wang, Michael; Feng, Lei; Fayad, Luis E.; Hagemeister, Frederick; McLaughlin, Peter; Rodriguez, M. Alma; Fanale, Michelle; Orlowski, Robert; Kwak, Larry W.; Neelapu, Sattva; Oki, Yasuhiro; et al.
Abstract : BACKGROUND: Although the outcomes of patients with mantle cell lymphoma (MCL) have improved, there is still no cure. Bortezomib has a 33% response rate in relapsed/refractory MCL and has shown additive and/or synergistic effects in preclinical trials with known effective agents. METHODS: This is a report of a prospective phase 2 trial of bortezomib added to rituximab plus hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone (BzR‐hyperCVAD)/rituximab, high‐dose methotrexate, and high‐dose cytarabine (BzR‐MA) for 95 patients with newly diagnosed MCL. RESULTS: The overall and complete response rates were 100% and 82%, respectively. Hematologic toxicity was high but expected and did not lead to an increased incidence of neutropenic fever or dose reductions in comparison with a similar reported regimen without bortezomib. After a median follow‐up of 44 months, the median overall survival had not been reached, and the time to treatment failure (TTF) was 55 months, which is not different from that of historical controls. CONCLUSIONS: BzR‐hyperCVAD/BzR‐MA at the dose and schedule studied produced high rates of response and a TTF similar to that of historical reports without bortezomib. Cancer 2018;124:2561‐9. © 2018 American Cancer Society . Abstract : The addition of bortezomib to rituximab plus hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone, alternating with rituximab, methotrexate, and cytarabine, produces high response rates and a time to treatment failure similar to that of historical reports without bortezomib.